Methodological and organizational features of construction of the training process in rowing - Gayratovna, I. R.; Mikhaylovich, K. V.; Ismoiljon, E.; Abduraxmanovna, A. M. (Miasto Przyszlosci, 2025)
Rowing is widespread throughout the world. The attractiveness of this sport lies in its versatile health benefits, which help improve the level of functional capabilities of the body.